The effects of initial stresses on nonlinear dynamic response of high arch dams subjected to far-field underwater explosion. (1st April 2022) - Pan, Xinhao; Wang, Gaohui; Lu, Wenbo; Yan, Peng; Chen, Ming; Gao, Zheng
Highlights: The coupled acoustic-structural method is employed to model the underwater explosion loading and the dam-reservoir-foundation interaction. The Concrete Damage Plasticity (CDP) model including the strain rate effect is used to model the concrete material behavior to blast loading. The influence of the initial stress from hydrostatic pressure and dead weight on the nonlinear dynamic response characteristics of a 300 m high arch dam subjected to far-filed underwater explosion are discussed. Abstract: Blast performance assessment of 300 m high arch dams is an important topic having been extensively studied in recent years. Because the arch dam is convex on the upstream face, the dam body is mainly in a compressive stress state under the action of upstream water pressure. However, due to the complexity of the problem, the initial stress is ignored in the blast response analysis of arch dams. For this purpose, the influence of initial stress on nonlinear dynamic response and failure modes of a 300 m high arch dam to the far-field underwater explosion has been studied in this paper. The acoustic-structural approach is employed to model the underwater explosion loading and the dam-reservoir-foundation interaction. The Concrete Damage Plasticity (CDP) model including the strain rate effect is used to model the concrete material behavior to blast loading. Damage development processes of high arch dams to the far-field underwater explosion are investigated. Nonlinear dynamic response characteristics of high arch dams with different initial stress states subjected to the far-field underwater explosion are discussed in terms of damage modes, residual displacement, and damage dissipated energy. The results show that the initial stress has a significant influence on the nonlinear dynamic and failure modes of high arch dams to the far-field underwater explosion. The initial stress state of high arch dams under hydrostatic pressure and deadweight should be the basic condition of blast response analysis.